On the Application of Educational Robotics to Children with Learning Disability - Silva, Maria Da Guia Torres Da; Curvelo, Carla Da Costa Fernandes; Gonçalves, Luiz M. G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
This paper introduces the results of an study on the possibility of application of Educational Robotics to the learning-teaching process of children with learning difficulty (or disability). We follow a surveying methodology, in which we have initially provided a form with questions for the students, professors, and monitors that have Educational Robotics activities in public schools of the municipality of Natal, Brazil, in order to analyze this possibility. After compiling the forms, we came out with some interesting results, that verifies the possibility of application with positive results. This is an important step towards showing the importance of educational robotics to Physicians and Educators, which are professionals that play an important role in this process, especially for children with learning disability. Jointly with roboticists that have been developing methodologies with cutting edge techniques and materials, they are turning educational robotics into a very useful resource for enhancing the learning-teaching process.